A comparative study to identify the impact of Fakir Lalon Shah’s ideology in modern vision management concept of the organisation - Mr. Supratim Chowdhury (Zien Journals, 2021)
Be it an organisational or individual, when vision (Goal) is set without the “SMART” concept there is every possible deviation in strategy formulation and execution of planned activities to achieve such vision. Deprived of an accurate vision neither an organisation nor an individual can function optimally and thus peace and harmony are jeopardized and disrupted.
Keywords: jeopardized; execution; accurate; strategy